Tanaman pembatas jalan di Kota Madiun sebagai bioreduktor logam berat Fe (besi) - Suproborini, Arum; Mochamad Soeprijadi Djoko Laksana, Mochamad Soeprijadi Djoko Laksana (Pharmed: Journal of Pharmaceutical Science and Medical Research, 2026)
Roadside plants are useful as pollutant absorbers (bioreductors), especially pollutants produced by motor vehicles. The purpose of this study was to determine the iron (Fe) content in roadside plants in Madiun city. This study used a survey method by taking plant leaf samples using a purposive random sampling method and analyzing the iron content with XRF (X-Ray Fluorescence). Based on the results of the study, the percentage of iron (Fe) content in Cordyline fruticosa L., Canna indica, Bougenvillea spectabilis, Chlorophytum cosmosum, Duranta repens, Equisetifolia sp, Saraca indica L., Agave gigantea, Ficus benyamina L., Sensevieria sp, Euphorbia hirta, Codiaeum variegatum, Ruellia tuberosa L., Graptophyllum pictum L., Syzygium oleiera plants ranged from 1.1319% - 11.5555%. Roadside plants are useful as iron (Fe) pollutant reducers.